Innovation Africa : emerging hubs of excellence - Adesida, Olugbenga; Karuri-Sebina, Geci; Resende-Santos, João, 1966- (Emerald Group Publishing Limited, 2016)
Innovation is critical to growth and development in Africa. In the context of a continent characterized by fast growing economies as well as an array of socioeconomic challenges, such as high levels of poverty, innovation in Africa must be understood in an encompassing manner. Africa needs to foster the emergence of its own Silicon Valley, but it must also foster the invention and adoption of more efficient wood-fueled traditional stoves that limit deforestation and combat climate change. This book contains a number of analytical case studies that examine the nature and origins of emerging high-end innovation hubs in Africa. These hubs are both understudied and little known inside and outside the continent. With this analysis, the book intends to highlight and draw lessons from some of the most promising and successful innovation cases in Africa today, exploring the key factors driving their successful emergence, growth and future prospects. Relevant for scholars, policymakers and business leaders, the book provides both inspiration and useful policy advice that can inform strategies and concrete measures to foster and speed up the pace of innovation in Africa today.